Prototipe Pembangkit Tenaga Surya Kapasitas 20 Watt Peak Sebagai Sumber Utama Tenaga Listrik Autonomous Buoy - Ahmad Nuryasin; Endi Permata (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to examine the use of 20 Watt Peak photovoltaic energy as the main power supply of the prototype on the autonomous buoy because it is able to absorb energy from direct sunlight. Experimental research methods are used to measure voltage, current, and electrical power on components such as photovoltaic, solar charger controller, battery, and electric motor. Tests were conducted by varying the motor speed to analyze the power usage and the time taken to recharge the battery in a span of 10 minutes, to identify factors affecting the performance of the autonomous float. The test results show that at 0% motor speed, no power is used as the motor is not rotating. However, at 25% motor speed, the motor started to use 50.93 watts of power. When the motor speed was 100%, there was a considerable increase in power consumption, where the power consumption increased to 112.86 watts. Thus, these results show that the higher the motor speed, the more power is required. The test shows the change in buoy voltage when not working or when charging for 10 minutes. At 0% motor speed, the initial voltage remains 12 Volts. When charged, the voltage remains 12 Volts because it is not being used. At 25-50% motor speed, the voltage drops from 10 Volts when charging to 12 Volts. At 75-100% motor speed, the initial voltage of 9-10 Volts rises to 10-11 Volts when charging. This shows an increase in voltage when the buoy is charging autonomously or when it is not working. The conclusion of this research is that an understanding of the energy usage performance of autonomous buoys is necessary to optimize the energy usage of 20 Watt peak photovoltaic as a renewable energy source.